The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/pmic.200401093
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of cellular proteins interacting with the hepatitis C virus core protein

Abstract: Hepatitis C virus (HCV) is a causative agent of chronic hepatitis and hepatocellular carcinoma. The core protein of HCV packages the viral RNA genome to form a nucleocapsid. In addition to its function as a structural protein, core protein is involved in regulation of cellular transcription, virus-induced transformation, and pathogenesis. To gain insights into cellular functions of the core protein by identification of cellular proteins interacting with the core protein, we employed a proteomic approach. Hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…35 Supportively, heterozygous mutations in K8 and K18 have been reported to be associated with various liver diseases, including cryptogenic cirrhosis, biliary atresia, hepatitis C or B, alcohol-induced cirrhosis, primary biliary cirrhosis and acute fulminant hepatitis. 36,37 In addition, proteomic analysis has revealed that K8 and K18 could interact with the core protein of hepatitis C virus, 38 and K8 induced autoantibodies among patients with HCC. 39 In this study, we provided the first evidence to show that the upregulation of K8 and K18 would contribute to the .…”
Section: Resultsmentioning
confidence: 99%
“…35 Supportively, heterozygous mutations in K8 and K18 have been reported to be associated with various liver diseases, including cryptogenic cirrhosis, biliary atresia, hepatitis C or B, alcohol-induced cirrhosis, primary biliary cirrhosis and acute fulminant hepatitis. 36,37 In addition, proteomic analysis has revealed that K8 and K18 could interact with the core protein of hepatitis C virus, 38 and K8 induced autoantibodies among patients with HCC. 39 In this study, we provided the first evidence to show that the upregulation of K8 and K18 would contribute to the .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being structural components of the virion, capsid proteins play roles in the virus replication cycle distinct from virion assembly (1,4,6,11,14,15,18,20,27). RUBV C participates in RNA synthesis in an apparent variety of ways.…”
Section: Rubella Virus (Rubv) (Family Togaviridae Genus Rubivirus)mentioning
confidence: 99%
“…Using a combination of affinity-based pull down experiments and mass spectrometric analysis, Kang and co-workers were able to determine that HCV core protein interacts with 14 host cell factors. 134 Some proteins that were identified include heat shock protein 60, implicated in modulation of apoptosis as well as fibrous cytoskeletal proteins, vimentin and cytokeratin 8. Sato et al also examined the lipid droplet proteomes of cells expressing HCV core proteins and found a number of interesting lipid droplet proteins as well as differential expression of certain proteins such as adipocyte differentiationrelated protein (ADRP) and tail-interacting protein of 47 kDa (TIP47).…”
Section: Proteomic Approachesmentioning
confidence: 99%
“…Recently proteomic approaches have been applied to study the differential protein expression during HCV protein expression, 61,134,135 replication and infection 136 as well as to discover biomarkers for HCC. [137][138][139][140] One of the first detailed proteomics study related to HCV biology was performed by Yan et al 141 In this study, they used isotope-coded affinity tags (ICAT) to examine differentially expressed proteins during interferon treatment of Huh-7 cells.…”
Section: Proteomic Approachesmentioning
confidence: 99%